Acoustic modelling of machines - ENGEL, Z.; STRYCZNIEWICZ, L. (Archives of Acoustics, 1999)
The vibro-acoustics modelling of machines and equipment sound fields occurring in industry has been presented in the paper. Several methods allowing the sound fiels modelling on the bases of a sound pressure and sound intensity measurements have been proposed. These methods allow to model the sound fields of actual sound sources located in a free field as well as a partially diffuse field. They are also useful in modelling of large industrial installations with linear sound sources. Mathematical dependencies, algorithms of modelling and examples of calculation results are included in the paper.